Pengembangan Media Pembelajaran Big Book Untuk Meningkatkan Keterampilan Berpikir Kritis Materi Rantai Makanan Kelas V SDN Mojodemak 2 - Ainun Nisa, Siti; Nuvitalia, Duwi; Januar Saputra , Henry (UNIB Press, 2024)
This study aims to determine the development of Big Book learning media as a supporting medium for learning science to improve critical thinking skills of food chain material class V SDN Mojodemak 2, and Determine the validity of the development of Big Book learning media to improve critical thinking skills of food chain material class V SDN Mojodemak 2. This type of research uses research of development (R&D) methods with the ADDIE model (analysis, design, development, implementation, evaluation). The result of the assessment of the development of Big Book learning media were declared valid. The validation test was carried out by two validators, media experts and material experts. The Big Book is said to be practical and acceptable based on the results of the responses of teachers and students in the field trial. The result of the assessment on the teacher’s response was 93,75% with the category “very feasible”. The result of the assessment on the student response was 98,25% with the category “very feasible”. Big Book learning media can be developed as one of the alternative learning media with other theme materials that are more detail and in accordance with learning outcomes and goals.